Synthesis of photochromic compounds for aqueous solutions and focusable light - Polyakova, Svetlana M. (2011)
Photochromic compounds with improved performance in pure water have been prepared and characterized. They possess an asymmetrical and extended conjugation system with a 1,2-bis(3-thienyl)perfluorocyclopentene core, additional thiophene rings connected with sulfonic acid residues, as well as terminal pyrid-4-yl and 4-alkoxyphenyl groups. A multistep synthetic route to a key compound with an amino group required for further derivatization has been developed. The complete photocyclization reaction of the initial "open ring" compound (with absorption maximum at 340 nm in MeOH or water) can be performed with a diode laser in pure water or aqueous buffer solutions (without added or-ganic solvents) under irradiation at 366-375 nm, and the reverse ring-opening reaction of the colored "closed ring" compound (λmax = 628 or 624 nm in MeOH or water) takes place under irradiation with visible green or red light (>500 nm). Building block 57, with a secondary amino group, can further be used in the synthesis of practically important, reversibly switchable, fluorescent compounds in which the fluorescent dye (donor) is attached to a photochromic unit (acceptor), and the resonant energy transfer from a donor to the colored form of an acceptor provides a reversible quenching of the fluorescence signal in aqueous solutions. © 2011 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.